Low-cost Na2ZrO3-based CO2 adsorbent and preparation method thereof

By using zirconium silicate as the source of zirconium, combined with alkali melting method and calcining method, a low-cost Na2ZrO3-based CO2 adsorbent was prepared, which solved the problem of high preparation cost in the prior art and achieved efficient and economical CO2 adsorption effect.

CN119733474AActive Publication Date: 2025-04-01HUAZHONG AGRI UNIV

Patent Information

Application Number
CN202510009338.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-01
Estimated Expiration
2045-01-03

AI Technical Summary

Technical Problem

The existing Na2ZrO3-based CO2 adsorbent has a high cost, mainly due to the high raw material cost of zirconium, which limits its economicality in large-scale applications.

Method used

By using the cheap zirconium silicate (ZrSiO4) as the zirconium source, combined with alkali melting and calcining, a low-cost Na2ZrO3-based CO2 adsorbent was prepared. The process involves reacting ZrSiO4 powder with a high concentration of sodium hydroxide solution, separating ZrO2 and Na2SiO3, and then mixing and calcining with Na2CO3 to form a Na2ZrO3-based CO2 adsorbent.

Benefits of technology

This process effectively reduces the preparation cost of Na2ZrO3-based CO2 adsorbent, improves its economy, and improves its high-temperature CO2 adsorption performance, which can meet the CO2 removal needs of industrial flue gas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119733474A_ABST
    Figure CN119733474A_ABST
Patent Text Reader

Abstract

The invention discloses a low-cost Na2ZrO3-based CO2 adsorbent and a preparation method of the low-cost Na2ZrO3-based CO2 adsorbent. The method comprises the following steps: (1) adding zirconium silicate powder and a heated high-concentration sodium hydroxide solution into a reaction kettle; (2) putting the closed reaction kettle into a muffle furnace for heating reaction; (3) taking out the reaction kettle, quickly cooling by water, carrying out solid-liquid separation on the product, collecting a filter cake, washing and drying; and (4) mixing and calcining the dried solid and sodium carbonate powder to obtain a target product. According to the method, low-cost zirconium silicate is used as a zirconium source, low-energy-consumption effective separation of Zr and Si in zircon sand is achieved through an alkali fusion method, the Na2ZrO3-based CO2 adsorbent is synthesized, the preparation cost of the adsorbent is effectively reduced, a technical basis is provided for resource utilization of subsequent separation products, and in addition, the method has the advantages of being simple in process, low in cost and good in application prospect. The prepared adsorbent has extremely strong CO2 adsorption performance at high temperature, and a new technical thought is provided for industrial application of the adsorbent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of adsorbent preparation, and more specifically, relates to a low-cost Na2ZrO3-based CO2 adsorbent and a preparation method thereof. Background Art

[0002] With the rapid development of industrialization and the increasing dependence of human beings on fossil energy, the concentration of CO2 in the atmosphere continues to rise, leading to an increasingly serious problem of global warming. In view of this reality, the most feasible solution is to develop low-cost, environmentally friendly, large-scale carbon capture, utilization and storage (CCUS) technology.

[0003] Carbon capture, utilization and storage (CCUS) technology is a comprehensive environmental engineering technology that integrates three key links: carbon capture, carbon utilization and carbon storage. Carbon capture is the first step of CCUS technology, which mainly captures CO2 from emission sources, which mainly includes capture before combustion, capture during combustion and capture after combustion. Carbon utilization is one of the important links of CCUS technology, which is to convert the captured CO2 into useful resources or energy, which mainly includes the production of chemical raw materials and conversion into clean energy. Carbon sequestration is also one of the important links of CCUS technology, which is to store CO2 underground or in the ocean for a long time in a certain way to avoid its release into the atmosphere, which mainly includes geological storage and marine storage. It can be seen that the effective development of carbon capture technology plays a key role in the development of CCUS technology. Therefore, the development of efficient CO2 adsorbents is of great significance.

[0004] In recent years, post-combustion capture technology based on high-temperature solid adsorption has demonstrated its strong industrial adaptability with its high carbon capture efficiency and low application cost, and has received widespread attention worldwide. Among the many high-temperature solid adsorbent materials, calcium-based adsorbents have large adsorption capacity and low material cost, but poor cycle stability, and are not economical in the long run. Lithium-based adsorbents have low regeneration energy consumption and high cycle stability, but their lithium source cost is high and they are not economical for large-scale application. Sodium-based adsorbents represented by Na2ZrO3 have been proven to have excellent cycle stability and a wider adsorption temperature window range, and are a high-temperature solid CO2 adsorbent material with great development potential. However, although the material cost of sodium-based adsorbents is generally lower than that of lithium-based adsorbents, the zirconium element in Na2ZrO3 is a transition metal element, and its reserves in nature are limited, resulting in the high cost of its raw materials (such as ZrO2, Zr(NO3)4), which greatly increases the difficulty of applying Na2ZrO3-based adsorbents. Therefore, developing a process route for preparing Na2ZrO3-based adsorbents based on low-cost zirconium sources has significant economic benefits and practical significance.

[0005] Zircon sand is an important zirconium industrial mineral, which is mainly produced in granite, alkaline rock and pegmatites or post-magmatic deposits related to these rocks. According to statistics, nearly 80% of the world's zircon sand is directly used in the foundry industry and the manufacture of refractory materials, and a small amount of zircon sand is used in alloys, paints, nuclear industry and other fields. In recent years, with the continuous development of the zirconium industry, zirconium-containing industrial waste has been continuously generated and accumulated, which has greatly promoted the iterative update and technological breakthrough of zirconium recycling technology. The in-depth development of the zirconium-containing industrial waste recycling industry provides a new way to achieve diversified supply and increase revenue and reduce expenditure, reduce the production cost of zirconium products, improve the ecological environment, and achieve a sustainable development industrial model.

[0006] Since zircon sand is directly used as the zircon source in most zircon product industries, it is inevitable that there will be a large amount of unreacted zircon sand in the final zirconium-containing waste. Its main component is zirconium silicate (molecular formula is ZrSiO4), and the theoretical composition is 67.21wt.% ZrO2 and 32.79wt.% SiO2. ZrSiO4 is the only and most stable compound in the ZrO2-SiO2 phase diagram. It has high resistance to thermal decomposition and acid decomposition, and is not easily wetted by molten metal. At extremely high temperatures (>2000℃), ZrSiO4 can be decomposed into ZrO2 and SiO2. It can be seen that ZrSiO4 can be used as a relatively cheap zirconium source to prepare Na2ZrO3, achieving a win-win situation in environmental benefits, social benefits and economic benefits. Summary of the invention

[0007] In view of the deficiencies of the above-mentioned prior art, the purpose of the present invention is to provide a low-cost Na2ZrO3-based CO2 adsorbent and a preparation method thereof; the present invention uses low-cost zirconium silicate as a zirconium source, realizes low-energy efficient separation of Zr and Si in zirconium silicate by alkali fusion method, and synthesizes Na2ZrO3-based CO2 adsorbent, which effectively reduces the preparation cost of the adsorbent and provides a technical basis for the subsequent resource utilization of the separated products. In addition, the prepared Na2ZrO3 has extremely strong CO2 adsorption performance, which provides a new technical idea for the industrial application of Na2ZrO3-based adsorbent; the present invention combines alkali fusion method and calcination method to realize the preparation of Na2ZrO3-based CO2 adsorbent, with low reaction temperature and energy saving. At the same time, the raw material price is low, which can reduce the application cost of the adsorbent and improve the economy of the adsorbent.

[0008] To achieve the above object, the present invention provides a method for preparing a low-cost Na2ZrO3-based CO2 adsorbent, comprising the following steps:

[0009] (1) adding ZrSiO4 powder and heated high concentration sodium hydroxide solution into a reaction kettle;

[0010] (2) placing the sealed reactor into a muffle furnace for heating reaction;

[0011] (3) taking out the reactor after heating, rapidly cooling it with water to separate the product into solid and liquid, collecting the filter cake, washing it in turn, and drying it;

[0012] (4) The dried solid is mixed evenly with Na2CO3 powder, and then placed in a muffle furnace for calcination to obtain the target product.

[0013] In the present invention, in step (1), the concentration of the sodium hydroxide solution is 70wt.%-77wt.%, and the sodium hydroxide solution is heated to above 97°C; the mass ratio of ZrSiO4 powder to the heated high-concentration sodium hydroxide is 1:25-1:15.

[0014] In the present invention, in step (1), the concentration of the sodium hydroxide solution is 75wt.%-77wt.%, and the mass ratio of ZrSiO4 powder to the heated high-concentration sodium hydroxide solution is 18:1-22:1.

[0015] In the present invention, in step (2), the heating temperature is 230-250° C. and the heating time is 10-30 h.

[0016] In the present invention, in step (3), the product is subjected to hot solid-liquid separation by a suction filtration device; the filter cake is washed with water, the drying temperature is 100-110° C., and the drying time is 6-20 hours.

[0017] In the present invention, in step (4), the solid after drying is ZrO2, and the molar ratio of the solid after drying to Na2CO3 powder is 1:1.1 to 1:1.2; the calcination temperature is 850-900°C, and the calcination time is 5h-8h.

[0018] The present invention also provides a low-cost Na2ZrO3-based CO2 adsorbent prepared by the above preparation method.

[0019] Furthermore, the present invention provides an application of a low-cost Na2ZrO3-based CO2 adsorbent in removing CO2 from industrial flue gas.

[0020] The principle of the present invention is as follows: low-cost ZrSiO4 is subjected to an alkaline fusion reaction with a high-concentration sodium hydroxide solution in a high-pressure reactor under certain temperature conditions to decompose ZrSiO4 into ZrO2 and Na2SiO3, and then the zirconium element and the silicon element in ZrSiO4 are separated by suction filtration, and the filter cake is the obtained ZrO2. Finally, the recovered ZrO2 is mixed with Na2CO3 in a certain molar ratio and calcined under high temperature conditions to obtain a Na2ZrO3-based CO2 adsorbent.

[0021] In general, the above technical solution conceived by the present invention has the following application advantages:

[0022] 1. ZrSiO4 has a lower price than ZrO2 and Zr(NO3)4, and is widely present in various industrial zirconium-containing wastes. Therefore, the zirconium-containing waste can be used for the preparation of adsorbents immediately after preliminary purification, which not only reduces the application cost but also realizes the full utilization of resources.

[0023] 2. It has been verified that the Na2ZrO3-based CO2 adsorbent prepared by this process has excellent high-temperature CO2 adsorption performance and can meet the CO2 removal needs of industrial flue gas. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is the X-ray diffraction pattern of the solid after drying of Example 1-5.

[0025] Figure 2 Example 1 X-ray diffraction pattern of the Na2ZrO3-based CO2 adsorbent finally prepared.

[0026] Figure 3 This is the temperature-dependent CO2 adsorption curve of the Na2ZrO3-based CO2 adsorbent finally prepared in Example 1.

[0027] Figures 4a-4f This is the isothermal CO2 adsorption curve of the Na2ZrO3-based CO2 adsorbent finally prepared in Example 1, and the adsorption temperatures are 600°C, 650°C, 700°C, 750°C, 800°C and 850°C respectively.

[0028] Figure 5a-5c This is the isothermal desorption curve of the Na2ZrO3-based CO2 adsorbent finally prepared in Example 1. The sample is first adsorbed to saturation in a pure CO2 gas flow at 850°C, and then desorbed in pure N2 gas flows at 850°C, 900°C and 950°C, respectively. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0030] The present invention provides a method for preparing a low-cost Na2ZrO3-based CO2 adsorbent, comprising the following steps:

[0031] (1) adding ZrSiO4 powder and a certain mass fraction of sodium hydroxide solution into a reactor according to a certain solid-liquid mass ratio;

[0032] (2) placing the reactor in a muffle furnace and heating it for a period of time;

[0033] (3) taking out the reactor after heating, cooling it with water quickly, separating the product into solid and liquid by a suction filtration device, collecting the filter cake, washing it with deionized water, and then placing the filter cake in an oven for heating and drying;

[0034] (4) The dried solid is mixed evenly with Na2CO3 powder in a certain mass ratio, and then placed in a muffle furnace for calcination to obtain the target product.

[0035] Among them, in step (1), the solubility of sodium hydroxide in water increases with increasing temperature, so it is necessary to control the temperature of the solution to achieve the preparation of a solution with a target mass fraction.

[0036] In step (2), the inner liner of the reaction kettle is made of polytetrafluoroethylene to meet the temperature tolerance requirements of the alkali fusion reaction conditions.

[0037] In step (3), the reaction kettle needs to be quickly cooled with water after being taken out of the muffle furnace, and then the filter cake is collected by hot filtration and washed several times with deionized water; the timing of filtration directly affects the effect of zirconium and silicon separation.

[0038] The main component of the solid after drying in step (4) is ZrO2, so it is set according to the mixed molar ratio of ZrO2 and Na2CO3, wherein Na2CO3 needs to be added by at least 10wt.% to reduce the effect of high-temperature sublimation of sodium on the purity of the reaction product.

[0039] Example 1

[0040] (1) Prepare a 77 wt.% sodium hydroxide solution in a constant temperature water bath (the temperature is maintained above 97° C. and the solution reaches a saturated state);

[0041] (2) ZrSiO4 powder and sodium hydroxide solution were then mixed in the reactor tank at a solid-liquid mass ratio of 20:1;

[0042] (3) After sealing the reactor, place it in a muffle furnace and heat it at 240°C for 24 hours;

[0043] (4) After heating is completed, the reactor is taken out and quickly rinsed with 20°C cold water to cool the metal shell, and then the metal shell of the reactor is opened. At this time, the temperature of the inner tank is still high, still higher than 90°C, and the product in the inner tank is separated into solid and liquid by a suction filter;

[0044] (5) During the filtration process, deionized water was added to wash 5 times, and then the filter cake was collected and heated and dried in an oven at a drying temperature of 105°C for 12 hours;

[0045] (6) The dried solid was mixed evenly with Na2CO3 powder in a mass ratio of 41:38.8, and then placed in a muffle furnace for calcination at a temperature of 900°C for 5 h.

[0046] In addition, the parameters of Examples 2 to 5 are specifically shown in Table 1, and the parameters not listed in the table are the same as those of Example 1.

[0047] Table 1

[0048]

[0049]

[0050] Experimental results analysis

[0051] The phase composition of the solid after drying in Example 1-5 was analyzed by X-ray diffraction (XRD). The results are as follows: Figure 1 As shown. It can be found that the mass fraction of sodium hydroxide has a significant effect on the phase composition of the alkali fusion product. Specifically, when the mass fraction of sodium hydroxide is 32.43wt.%, the alkali fusion reaction hardly occurs. As the alkali concentration gradually increases, the diffraction peak of ZrSiO4 gradually weakens, and the diffraction peak of Na2ZrSiO5 gradually becomes significant. When the mass fraction of sodium hydroxide exceeds 60wt.%, the diffraction peak of ZrSiO4 is almost invisible, which can be regarded as ZrSiO4 being completely converted into Na2ZrSiO5. When the mass fraction of sodium hydroxide exceeds 75wt.%, the diffraction peak of Na2ZrSiO5 disappears, and the main component of the product is ZrO2. At this time, zirconium and silicon in ZrSiO4 are completely separated.

[0052] The elemental composition of the sample in Example 1 before and after alkali fusion was analyzed by X-ray fluorescence spectrometer (XRF), and the results are shown in Table 2. It can be found that after the alkali fusion reaction, the Si element content of the solid phase product decreased from 13.09% to 8.13%, and the Na element content increased from 0.02% to 8.52%.

[0053] Table 2

[0054]

[0055] The phase composition of the Na2ZrO3-based CO2 adsorbent finally prepared in Example 1 was analyzed by X-ray diffraction (XRD). The results are as follows: Figure 2As shown. It can be seen that a strong diffraction peak of Na2ZrO3 was detected in the final sample, which further illustrates that the solid phase product after alkali fusion recovery is ZrO2 with high purity.

[0056] The temperature-dependent CO2 adsorption performance of the Na2ZrO3-based CO2 adsorbent prepared in Example 1 was tested by thermogravimetric analyzer (STD-Q600). Figure 3 As shown. It can be found that when the temperature slowly rises to 300℃, the mass growth rate of the sample first increases and then decreases, and a peak appears at 300℃. As the temperature continues to rise, the mass continues to increase. When the temperature rises to about 800℃, the mass growth rate surges to 900℃, indicating that 800-900℃ is the optimal CO2 adsorption temperature range of the adsorbent. When the temperature continues to rise, the mass growth of the sample gradually slows down, reaching the maximum mass at about 1000℃, and then the mass begins to decrease continuously, entering the CO2 desorption stage.

[0057] The isothermal CO2 adsorption performance of the Na2ZrO3-based CO2 adsorbent prepared in Example 1 was tested by thermogravimetric analyzer (STD-Q600). Six temperatures in the range of 600-850°C were selected for isothermal adsorption tests under pure CO2 gas flow. The corresponding isothermal adsorption curves are shown in Figure 2. Figures 4a-4f As shown. It can be found that the entire adsorption process can be divided into three stages. The first stage is very short, and the mass of the adsorbent in the corresponding interval increases at an accelerated rate; the second stage is longer than the first stage, the mass of the adsorbent increases at a steady rate, and the growth rate remains almost unchanged; the third stage is the longest, the mass of the adsorbent continues to rise, but the growth rate gradually decreases. It is worth noting that when the adsorption temperature is 850℃, the third stage occupies almost the vast majority of the entire process, and the final mass almost stops growing at this time, that is, there is a threshold for the CO2 adsorption amount.

[0058] The isothermal CO2 desorption performance of the Na2ZrO3-based CO2 adsorbent prepared in Example 1 was tested by thermogravimetric analyzer (STD-Q600). Three temperatures in the range of 850-950°C were selected for isothermal adsorption tests under pure N2 gas flow. The corresponding isothermal adsorption curves are shown in Figure 2. Figure 5a-5c By comparison, it can be found that the higher the desorption temperature, the shorter the time required for complete desorption and regeneration of the adsorbent, and under the temperature condition of more than 850°C, the adsorbent can be completely regenerated within 25 minutes.

Claims

1. A method for preparing a low-cost Na2ZrO3-based CO2 adsorbent, characterized in that: The following steps are involved: (1) Adding ZrSiO4 powder and heated high-concentration sodium hydroxide solution into a reactor; (2) placing the sealed reactor into a muffle furnace for heating reaction; (3) After heating, the reactor is taken out, and the product is quickly cooled by water to separate the solid and liquid, and the filter cake is collected, washed and dried in sequence; (4) The dried solid is mixed evenly with Na2CO3 powder and then placed in a muffle furnace for calcination to obtain the target product.

2. The preparation method according to claim 1, characterized in that In step (1), the concentration of the sodium hydroxide solution is 70 wt.%-77 wt.%, and the sodium hydroxide solution is heated to above 97° C.; the mass ratio of ZrSiO4 powder to the heated high-concentration sodium hydroxide is 1:25-1:

15.

3. The preparation method according to claim 1, characterized in that: In step (1), the concentration of the sodium hydroxide solution is 75 wt.%-77 wt.%, and the mass ratio of ZrSiO4 powder to the heated high-concentration sodium hydroxide solution is 1:22-1:

18.

4. The preparation method according to claim 1, characterized in that In step (2), the heating temperature is 230-250° C. and the heating time is 10-30 h.

5. The preparation method according to claim 1, characterized in that In step (3), the product is separated into solid and liquid by a suction filtration device while hot; the filter cake is washed with water, the drying temperature is 100-110°C, and the drying time is 6-20 h.

6. The preparation method according to claim 1, characterized in that: In step (4), the solid after drying is ZrO2, and the molar ratio of the solid after drying to Na2CO3 powder is 1:1.1~1:1.2; the calcination temperature is 850-900°C, and the calcination time is 5h-8h.

7. Use of a low-cost Na2ZrO3-based CO2 adsorbent prepared by the preparation method as claimed in any one of claims 1 to 6 in removing CO2 from industrial flue gas.

Citation Information

Patent Citations

  • Process for hydrothermally preparing zirconium oxychloride with low alkali consumption

    CN103011278A

  • Low-temperature liquid phase decomposition method for zircon sand

    CN105236481A

  • Synthesizing and application methods of sodium zirconate

    CN109574072A

  • Performance-enhanced Na2ZrO3-based CO2 adsorbent as well as preparation method and application thereof

    CN118267966A

  • Carbon dioxide capture articles and methods of making same

    US20180361352A1

Cited By

  • Integrated method and system for circulating hydrogen production and light condensation heat storage based on multifunctional catalysis-adsorbent sodium zirconate

    CN122010048A